Carbon and hydrogen radio recombination lines from the cold clouds towards Cassiopeia A - Oonk, J; van Weeren, R; Salas, P; Salgado, F; Morabito, L; Toribio, M; Tielens, A; Röttgering, H (Oxford University Press, 2017)
We use the Low Frequency Array to perform a systematic high spectral resolution investigation of the low-frequency 33–78 MHz spectrum along the line of sight to Cassiopeia A. We complement this with a 304–386 MHz Westerbork Synthesis Radio Telescope observation. In this first paper, we focus on the carbon radio recombination lines. We detect Cnα lines at −47 and −38 km s−1 in absorption for quantum numbers n = 438–584 and in emission for n = 257–278 with a high signal-to-noise ratio. These lines are associated with cold clouds in the Perseus spiral arm component. Hnα lines are detected in emission for n = 257–278. In addition, we also detect Cnα lines at 0 km s−1 associated with the Orion arm. We analyse the optical depth of these transitions and their linewidth. Our models show that the carbon line components in the Perseus arm are best fitted with an electron temperature of 85 K and an electron density of 0.04 cm−3 and can be constrained to within 15 per cent. The electron pressure is constrained to within 20 per cent. We argue that most of these carbon radio recombination lines arise in the CO-dark surface layers of molecular clouds, where most of the carbon is ionized, but hydrogen has made the transition from atomic to molecular. The hydrogen lines are clearly associated with the carbon line emitting clouds, but the low-frequency upper limits indicate that they likely do not trace the same gas. Combining the hydrogen and carbon results, we arrive at a firm lower limit to the cosmic-ray ionization rate of 2.5 × 10−18 s−1, but the actual value is likely much larger.